The impact of COVID-19 on the relationship between governance and society: evidence from an online survey - Ciobanu, Rodica; Roșca, Mariana (My University, 2021)
In order to understand the impact of the COVID-19 pandemic on the relationship between governance and society, we surveyed approximately 500 Moldovans using an online instrument designed to recover the causal impact of the pandemic on the relationship between Moldovan citizens, the current governance and expected outcomes. Results show large negative effects across many dimensions. The article highlights how the relationship between government and citizens developed during the pandemic and underlines some vulnerabilities of Moldovan society which were also present before COVID-19, but intensified during the crisis. Due to COVID-19, 41,5% of Moldovans have changed their lifestyle and 88,4% argue that their situation is worst due to the fact that the pandemic crisis deepened the previous social, political and economic crises of the country. Finally, 35.4% of respondents point out to quite high levels of inefficient communication as well as contradictory information of governmental institutions and 75,5% consider there is a persisting lack of transparency in governmental communication during the pandemic crisis. Thus, we show that the economic and health-related shocks induced by COVID-19 expanded systematically on the society as a whole, with large negative effects on the relationship between governance and society.
Keywords: COVID-19; governance; citizens; crises; social order